KINERJA UMKM: PERAN ORIENTASI KEWIRAUSAHAAN SEBAGAI VARIABEL MEDIASI ANTARA PELATIHAN DAN KOMPETENSI KEWIRAUSAHAAN DI KOTA YOGYAKARTA - Prawita, Dika; Lysander, Mohammad Ahyar Syafwan; Azwar, Azwar; Hartono, M. Edhie (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to fill the research gap between competitive advantage, HR competency, entrepreneurial orientation, and business performance. This sampling was carried out using a purposive sampling technique. Purposive Sampling is determining samples based on certain criteria, where the research carried out sampling based on certain criteria, namely all MSME actors in Yogyakarta City, MSME actors who are 17-45 years old and have been running the MSME business for at least 2 years and have an education level of at least junior high school/equivalent level. The data analysis technique in this research is quantitative. The data analysis process can be carried out using a computer with the SPSS application, in order to have a competitive advantage, produce precise and accurate information and, be an addition to the literature and publication of the accredited national journal Sinta 3 in 2023. The research results prove that all the variables tested have a positive and significant effect on results of regression 1 and regression 2.